Hydrogen in Patients With Corticosteroid-Refractory/Dependent Chronic Graft-Versus-Host-Disease: A Single-Arm, Multicenter, Open-Label, Phase 2 Trial - Qian, Liren; Liu, Miao; Shen, Jianliang; Cen, Jian; Zhao, Defeng (Frontiers in Immunology, 2020)
Chronic graft-versus-host-disease (cGVHD) is the leading cause of late non-relapse mortality after allogeneic hematopoietic stem cell transplantation(HSCT). There is no standard therapy for patients refractory or dependent to corticosteroid treatment. We hypothesized that hydrogen may exert therapeutic effects on cGVHD patients with few side effects. A prospective open-label phase 2 study of hydrogen was conducted. Patients received hydrogen-rich water 4ml/kg orally three times a day. Responses were graded in the skin, mouth, Gastrointestinal(GI), liver, eyes, lungs and joints and fascia every 3 months. A total of 24 patients (median age 27) were enrolled. Of the 24 patients, 18 (75%; 95% CI, 55.1% to 88%) had an objective response. No significant toxicity was observed. The estimated 4-year overall survival rate was 74.7%(95% CI, 54.9%–94.5%). The survival time was significantly prolonged in the response group. The survival rate at 4 years in the response group is significantly higher than the nonresponse group (86.6% vs 0%; p= 0.000132). Hydrogen showed great efficacy on cGVHD patients and long-term administration of hydrogen was not associated with significant toxic effects. The trial was registered at www.ClinicalTrials.Gov, NCT02918188.